Understanding governance in contemporary Japan : transformation and the regulatory state - Mogaki, Masahiro (Manchester University Press, 2019)
This book explores the transformation of Japan's state in response to the challenges of governance by focusing on the case studies of ICT regulation and antimonopoly regulation after the 1980s as an example of the new governance school in Japanese politics and beyond.